Disentangling the role of deviant letter position on cognate word processing - Comesaña, Montserrat (2021)
The datasets presented in this study can be found in online repositories. The names of the repository/repositories and accession number(s) can be found at: https://osf.io/mqhu5/?view_only=94cdf0d86e0b4e7e8b2757e33f6a78ce.